Economic and Health Predictors of National Postpartum Depression Prevalence: A Systematic Review, Meta-analysis, and Meta-Regression of 291 Studies from 56 Countries - Hahn-Holbrook, Jennifer; Cornwell-Hinrichs, Taylor; Anaya, Itzel (Frontiers in Psychiatry, 2018)
Background: Postpartum depression (PPD) poses a major global public health challenge. PPD is the most common complication associated with childbirth and exerts harmful effects on children. Although hundreds of PPD studies have been published, we lack accurate global or national PPD prevalence estimates, and have no clear account of why PPD appears to vary so dramatically between nations. Accordingly, we conducted a meta-analysis to estimate the global and national prevalence of PPD, and a meta-regression to identify economic, health, social or policy factors associated with national PPD prevalence. Methods: We conducted a systematic review of all papers reporting PPD prevalence using the Edinburgh Postnatal Depression Scale. PPD prevalence and methods were extracted from each study. Random effects meta-analysis was used to estimate global and national PPD prevalence. To test for country level predictors, we drew on data from UNICEF, WHO, and the World Bank. Random effects meta-regression was used to test national predictors of PPD prevalence. Findings: 308 studies of 304,449 women from 56 countries were identified. The global pooled prevalence of PPD was 17.5% (95% CI: 16.4% - 18.6%), with significant heterogeneity across nations (Q = 17,192, p = .000, I2 = 98%), ranging from 3.10% (0.01% - 10.87%) in Singapore to 37.78% (30.95% - 44.83%) in Chile. Nations with significantly higher rates of income inequality (R2=42.78%), maternal mortality (R2=25.54%) infant mortality (R2=12.23%), total fertility rates (R2=17.14%), or women of childbearing age working > 40 hours a week (R2=24.14%) have higher rates of PPD. Together, these factors explain 77.26%% of the national variation in PPD prevalence. Interpretation: The global prevalence of PPD is greater than previously thought and varies dramatically by nation. Disparities in wealth inequality and maternal-child-health factors explain much of the national variation in PPD prevalence.